High Accuracy Homodyne Interferometric Method for Wide Dynamic Range Applications - Carneiro, Alexander C.; Lopez-Barbero, Andres P.; Silva, Vinicius N. H.; Kitano, Claudio [UNESP]; Galeti, Jose H.; Santos, Alexandre Bessa dos (Ieee-inst Electrical Electronics Engineers Inc, 2020)
In this paper a new method for the detection of optical phase in passive homodyne interferometers, with high accuracy and wide dynamic range is presented. Unlike the traditional and more recent methods, which use between 3 and 6 harmonic components to calculate the modulation index, the proposed method uses only 2 harmonic components. Because of this, the method has higher accuracy in the presence of noise compared to other methods known in the literature. Further, the method has the advantage of not requiring knowledge of the phase of the excitation signal. The numerical implementation is simple, since it uses a 3rd order polynomial fit for the calculation of the modulation index. For the experimental verification of the method, a configuration based on an unbalanced Mach-Zehnder interferometer (MZI) was used, which resulted in a dynamic range for the modulation index from 8.38 to 16.76 rad. It is important to note that these limits can be easily expanded by means of adaptations of the optical and electronic setup depending on the characteristics of the excitation signal. The proposed method can be used in several applications, such as pressure measurements, vibration, displacement, etc.
Keywords: Passive homodyne interferometers; optical phase detection method; high accuracy; wide dynamic range